Numerical and experimental study of mixed flow pump as turbine for remote rural micro hydro power plant application - Sarid Mejiartono; Muhammad Fathul Hikmawan; Aditya Sukma Nugraha (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2022)
The use of a pump as opposed to a turbine/pump as turbine (PAT) for off-grid electrification applications is one of the important ways to be considered in efforts to equalize electrical energy in Indonesia. The main problem in PAT applications is how to predict pump performance if applied as a turbine to find out its best characteristics and efficiency points. This study discusses a method to find pump performance specifications when using a pump with a mixed flow type as a turbine for Micro Hydro Power Plants. The numerical method by utilizing computational Fluid Dynamics (CFD) based software simulations that have been proven to be accurate according to previous studies was selected for use in obtaining predictions of the pump characteristics as turbines. Then the PAT characteristics of the CFD simulation results are validated by conducting direct testing. The results of the CFD numerical simulation using ANSYS Fluent software show the performance curve of a mixed flow pump operated as a turbine at various rotating speeds. The highest efficiency for each rotating speed ranges from 35-40%. The test results directly show the PAT characteristics, that the performance range is close to the numerical simulation results with a difference of 10%.